2022
DOI: 10.3390/ijms23074000
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Inclusion Complexes: Molecular Interactions of Hesperidin and Hesperetin with HP-Β-CD and Their Biological Effects

Abstract: This study aimed at obtaining hesperidin (Hed) and hesperetin (Het) systems with HP-β-CD by means of the solvent evaporation method. The produced systems were identified using infrared spectroscopy (FT-IR), X-ray powder diffraction (XRPD), and differential scanning calorimetry (DSC). Moreover, in silico docking and molecular dynamics studies were performed to assess the most preferable site of interactions between tested compounds and HP-β-CD. The changes of physicochemical properties (solubility, dissolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 81 publications
7
36
0
Order By: Relevance
“…To our knowledge, research on the amorphization of hesperidin can be considered as one of the pioneering processes to improve its solubility. For example, Wei et al obtained amorphous hesperidin using the wetness impregnation method [ 21 , 22 ], Wdowiak et al obtained amorphous inclusion complex by solvent evaporation [ 23 ]. Nevertheless, other techniques have been widely used to improve the solubility of hesperidin [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, research on the amorphization of hesperidin can be considered as one of the pioneering processes to improve its solubility. For example, Wei et al obtained amorphous hesperidin using the wetness impregnation method [ 21 , 22 ], Wdowiak et al obtained amorphous inclusion complex by solvent evaporation [ 23 ]. Nevertheless, other techniques have been widely used to improve the solubility of hesperidin [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of the water solubility and antioxidant activity have been reported on hesperidin mixed with chitooligosaccharide [ 13 ]. It has also been reported that inclusion complexes of hesperidin or hesperetin with hydroxypropyl β-cyclodextrin increase solubility and antioxidant potential [ 14 ]. Glycosylation of hesperidin or hesperetin has been studied and is considered an efficient and promising method to increase solubility and bioavailability [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Corciova et al [ 63 ] also reported that complexing hesperidin with HP-β-CD resulted in improved dissolution as well as antioxidant and antibacterial properties. Similarly, complexing hesperetin with β-CD and HP-β-CD enhances the dissolution rate and improves solubility, along with anti-inflammatory and cytotoxicity effects on cancer cell lines [ 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%